Fenomena Taubat dan Hijrah di Kalangan Komunitas Sahabat Hijrahku di Kelurahan Babura Kecamatan Medan Sunggal - Zikri, Paisal; Syukri, Syukri; Damanik, Nurliana (Lembaga Yasin AlSys, 2023)
Babura Village is one of the different Villages in the Medan Sunggal District area. Medan City, North Sumatra Province, which still has a Muslim minority in every corner of the region. after the author made observations, it was found that in the Kelurahan there is a community called Community of Friends of Hijrahku which was founded by Ahmad Kami in Babura Village, Medan Sunggal District, North Sumatra. , removing the partition of differences between Harakah without violating the Shari'a and imparting knowledge and skills to the community according to Islamic and Shari'a values.